Dialog Pemahaman Perkawinan antara Katolik dan Protestan: Kemungkinan untuk berbagi dan melengkapi demi Kerajaan Allah - Sugandi, Pera Arif (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
The concept and understanting of marriage in Christianity (Catholic and Protestant churches) based on the marriage of the couple that cannot be separated. Yet the approach of moral influence how the marriage application should eventually divorce. Moral approach is input for each of the Church, considering a case by case basis, so that marriage law should be able to answer in a new language and relevant to the context at hand. Dialogue to discuss and share about the application of this moral approach is treasures in the Church of Christ. This wealth should be marked humility, a willingness to learn from each other and away from judgment. Each party must have the humility to be amazed by the other as a gift from God, which sometimes are not discussed in detail by each church. The dialogue on the concept of marriage is indissoluble, reinforces the identity of each church without fear of being threatened by the other. The laws are not seen normatively but in situation of compassion and deep meaning.